2008
DOI: 10.1021/ja800731k
|View full text |Cite
|
Sign up to set email alerts
|

Organogel Formation by a Cholesterol-Stoppered Bistable [2]Rotaxane and Its Dumbbell Precursor

Abstract: The switching properties, gelation behavior, and self-organization of a cholesterol-stoppered bistable [2]rotaxane containing a cyclobis(paraquat-p-phenylene) ring and tetrathiafulvalene/1,5-dioxynaphthalene recognition units situated in the rod portion of the dumbbell component have been investigated by electrochemical, spectroscopic, and microscopic means. The cyclobis(paraquat-p-phenylene) ring in the [2]rotaxane can be switched between the tetrathiafulvalene and 1,5-dioxynaphthalene recognition units by ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 45 publications
2
74
0
4
Order By: Relevance
“…[61][62][63][64][65] The self-assembled molecular wires of a TTF gel (24, Scheme 7) was introduced in 1994 by Jørgensen and coworkers. [66] Bryce et al have reported the first experimental demonstration of a conductive TTF gel using spin-coated films of 25.…”
Section: Angewandte Minireviewsmentioning
confidence: 99%
“…[61][62][63][64][65] The self-assembled molecular wires of a TTF gel (24, Scheme 7) was introduced in 1994 by Jørgensen and coworkers. [66] Bryce et al have reported the first experimental demonstration of a conductive TTF gel using spin-coated films of 25.…”
Section: Angewandte Minireviewsmentioning
confidence: 99%
“…containing two different stations) [2]rotaxane 44 stoppered by cholesterol units was performed. 30 The switching properties, gelation behavior and self-organization of 44 have been investigated, and compared with those of its dumbbell 45 (i.e. 44 without the ring).…”
Section: Scheme 13mentioning
confidence: 99%
“…23,24 However, TTF-based gelators with cholesterol groups are scarcely described. Stoddart et al 25 have just recently reported TTF-based rotaxane with cholesterol groups and the resulting organogels. Herein we want to report a new TTF derivative with two cholesterol groups (compound 1 in Scheme 1).…”
Section: -14mentioning
confidence: 99%